Educação e moral na Filosofia de Éric Weil - Assis, Aparecido de (2011)
This thesis aims to examine the theme education and morals in the three philosophical Works of Eric Weil: Logic of Philosophy, Moral Philosophy and Political Philosophy. For Weil, education can only be justified if it is based on morality, according to the purpose for which it is intended, which is to lead man to a moral reflection through reason. The reflection seeks to solve the conflict on man with his empirical character, which he presents himself as being an immoral and violent. Weil characterized the violence as contrary to reason, that is, as negation of coherent discourse. However, violence is understood in two senses: negative and positive. In a negative sense, it is pure violence, radical, which must be combated. In this sense, it is understood as violence against the moral, humanitarian and community of people living in the community. In a positive sense, it is the use of reason to transformation of a violent man to be reasonable. As an educator, philosopher makes use of positive violence to eliminate negative violence, thus promoting non-violence in society. This is the ultimate meaning of moral education